Offenes Kulturhaus 1992-1995. - Habringer, Rudolf; Mitgutsch, Anna; Sturm, Martin; Offenes Kulturhaus, Linz (Linz : Offenes Kulturhaus des Landes OÖ, 1995)
Overzicht tentoonstellingen Offenes Kulturhaus des Landes OÖ Linz 1992-1995
Ahrendt, Susanne ; Bartel, Christian ; Bitter, Sabine ; Cella, Bernhard ; Konrad, Aglaia ; Nussbaumer, Georg ; Ulrichs, Timm ; Weber, Helmut ; Bielz, Gudrun ; Bove, Antonino ; Hazelwander, Karin ; Leikauf, Andreas ; Jurtschitsch, Aurelia Llois ; Lobnig, Hubert ; Moser, Maria ; Moser-Wagner, Gertrude ; Preisinger, Wolfgang ; Vasicek, Brigitte ; Reiter, Josef ; Sodomka, Andrea ; Math, Norbert ; Thürkauf, Verena ; Bodnar,Eva Eszter ; Dick, Inge ; Kuchenbrod, Marion ; Jaszcza, Richard ; Kucznierz, Guido ; Persson, Marga ; Schicker, Maria ; Schuster, Robert ; Schwaiger, Josef ; Zemrosser, Susanne ; Kaufmann, Dieter ; Martin, Gottfried ; Rabl, Günther ; Jessl, Rainer ; Neulinger, Gerhard ; Hufnagl, Martina ; Hutterer, Claudia ; Radl, Gertrud ; Schepe, Christian ; Starlinger, Johanna ; Steiner, Thomas ; Hollinetz, Klaus ; Pichler, Georg ; Preisel, Dieter ; Pilar, Walter ; Zsambok, Gerhard ; Steinbacher, Christian ; Berger, Gabriele ; Meusburger, Herbert ; Bouchet, Pascal ; Neuber, Ute ; Pramhas, Thomas ; Schatzl, Leo ; Westerfrölke, Anja ; Spackman, Betty ; Bäcker, Heimrad ; Bott, Karsten ; Herter, Renate ; Hubbard & Birchler ; Karner, Andreas ; Kruk, Mariusz ; Lipton, Hilmar ; Mascher, Friedrich ; Plank, Claudia ; Poschauko, Hans Werner ; Rheinsberg, Raffael ; Tragut, Bernhard ; Berghold, Gundi ; Birnbaum, Dara ; Gallée, Ilia ; Graf, Franz ; Astuy, Christy ; Thorarinsson, Bjarni H. ; Hinterberger, Norbert ; Kabakov, Ilya ; Kosuth, Joseph ; Pavlik, Wolfgang ; Steinbach, Haim ; Maier, Karl-Heinz ; Moser, Johann ; Schuster, Robert ; Riepl, Peter ; Moser, thomas ; Arnold, skip ; Black Market International ; Fritz, Jürgen ; Jelinek, Robert ; Kaltenbacher, Charles ; Kawazu, Marie ; Kosa, Attila ; MacLennan, Alastair ; Nieslony, Boris ; van Poppel, Jacques ; Rolfe, Nigel
Ruller, Tomas ; Vaara, Roi ; Zegveld, Peter ; van der Poll, Thijs ; Bachheimer, Jarno ; Caspar, Andreas B. ; Gauss, Brigitte ; Geccelli, Martina ; Jaritz, Horst ; Kienesberger, Hans ; Musil, Wolfgang ; Rodler, Andreas ; Ablinger, Peter ; Herndler, Christoph ; Mashayekhi, Nader ; Gerngross, Heidulf ; Löcker, Brigitte ; Prinzgau/podgorschek ; Tschapeller, Wolfgang ; Ventimiglia, Timm ; Wörndl, Hans Peter ; Pamminger, Walter ; Export, Valie ; Frenkel, Vera ; Geismar, Jarg ; Haider, Ilse ; Heinisch, Barbara ; Jones, Joanna ; Herter, Renate ; Johannsen, Ulrike ; Klonaris, Maria ; Thomadaki, Katerina ; Mansell, Alice ; Nathan, Piotr ; Radenhausen, Silke ; Wid, Udo ; Burkert, Cornelius ; Iranzo, José ; Ivekovic, Sanja ; Meierhofer, Christine ; Nebel, Christoph ; Heger, Swetlana ; Dejanov, Plamen ; Matt, Hubert ; Pamminger, Klaus ; Pauli, Thomas N. ; Rucci, A.A. ; Barreiro, A. Harold ; Bartol, Damir ; Bhagwati, Sandeep ; van Doren, Miryam ; Lang, Bernhard ; Loidl, Christian ; Muthspiel, Christian ; Schäfer, Sabine ; Krebs, Joachim ; Sharp, Elliott ; Spour, Robert ; Obermaier, Klaus ; Williams, Phil ; Blume, Anna ; Blume, Bernhard Johannes ; Bruch, Klaus vom ; Erismann, Marc ; Krystufek, Elke ; Lewitscharoff, Sibylle ; Merrit, Just ; Niedermayr, Walter ; Stalder, Anselm ; Barbier, Gilles
Engels & Duits
boek